Two decades of Martini - Marrink, Siewert J. (2023)
Funding Information: Work in DPTs group is supported by the Natural Sciences and Engineering Research Council (Canada). Further support came from the Canada Research Chairs program. Riccardo Alessandri is supported by the Dutch Research Council (NWO Rubicon 019.202EN.028). Luca Monticelli is supported by the French National Institute of Health and Medical Research (INSERM). Paulo C. T. Souza is supported by French National Center for Scientific Research (CNRS). Further funding of Paulo C. T. Souza and Luca Monticelli came from a research collaboration with PharmCADD. Siewert J. Marrink is supported by an Advanced Grant (COMP‐O‐CELL) from the European Research Council. Publisher Copyright: © 2022 The Authors. WIREs Computational Molecular Science published by Wiley Periodicals LLC.